2020
DOI: 10.1038/s41556-020-0483-2
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 promotes naive pluripotency through Neo1 and Unc5b co-regulation of Wnt and MAPK signalling

Abstract: In mouse embryonic stem cells (mESCs), chemical blockade of Gsk3α/β and Mek1/2 (2i) instructs a self-renewing ground state whose endogenous inducers are unknown. Here we show that the axon guidance cue Netrin-1 promotes naive pluripotency by triggering profound signalling, transcriptomic and epigenetic changes in mESCs. Furthermore, we demonstrate that Netrin-1 can substitute for blockade of Gsk3α/β and Mek1/2 to sustain self-renewal of mESCs in combination with leukaemia inhibitory factor and regulates the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
1
28
1
2
Order By: Relevance
“…In this study, we found not only interaction between NEO1 and FAK but also the induction of FAK Y397 phosphorylation when cells are treated with exogenous NTN1. Importantly, our results are in line with recent data published by Huyghe et al, who indicated that NTN-1 signaling through NEO1 promotes FAK activation in mouse embryonic stem cells [16]. In addition, p-FAK Y397 inhibitor reduces cell migration of control cells to a similar extent when compared to NEO1 knock-down cells in a cell migration assay, indicating that FAK is downstream of the NEO1 signaling pathway.…”
Section: Mechanisms Associated To Neo1/ntn1 Complex Association With supporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found not only interaction between NEO1 and FAK but also the induction of FAK Y397 phosphorylation when cells are treated with exogenous NTN1. Importantly, our results are in line with recent data published by Huyghe et al, who indicated that NTN-1 signaling through NEO1 promotes FAK activation in mouse embryonic stem cells [16]. In addition, p-FAK Y397 inhibitor reduces cell migration of control cells to a similar extent when compared to NEO1 knock-down cells in a cell migration assay, indicating that FAK is downstream of the NEO1 signaling pathway.…”
Section: Mechanisms Associated To Neo1/ntn1 Complex Association With supporting
confidence: 93%
“…The DCC/NEO1 receptors act as homodimers or form heterodimers with the UNC5 receptor family, sharing their binding to the Netrin ligands [15]. Netrin-1 (NTN1) is the best characterized Netrin ligand, and has been shown to interact with NEO1, leading to axonal guidance and cell migration, as well as cell-tocell adhesion and self reneval [11,16]. The binding between NTN1 and NEO1 involves FNIII domains 4 and 5 of NEO1 [17].…”
Section: Introductionmentioning
confidence: 99%
“…For the generation of MEF lines stably expressing WT or mutant hTSC1, a modified sleeping-beauty-based vector, pITR-TTP2, was used. The original pITR-TTP vector, and the associated pCMV-Transposase vector, were a kind gift of Manuel Koch and Rolf Marschalek (described in (Huyghe et al, 2020;Kowarz et al, 2015;Wang et al, 2018)), in which the 3 0 multiple cloning site (MCS) was expanded by double-stranded oligo cloning to generate pITR-TTP2. The pITR-TTP2-hTSC1 WT and M1 mutant coding sequences were PCR amplified from pcDNA3-hTSC1 vectors and subcloned into pITR-TTP2.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Mechanistically, we identify the Unc5B intracellular UPA domain as a regulator of LRP6 interaction, suggesting that the UPA domain may induce LRP6 phosphorylation through recruitment of kinases or other mechanisms that remain to be determined. Recent studies in naïve pluripotent embryonic stem cells showed that Netrin1 binding to Unc5B induced FAK-mediated phosphorylation of GSK3α/β, a kinase implicated in LRP6 activation 38 , suggesting one possible mechanism. Finally, because Unc5B is expressed in arterial and capillary endothelium, but not in veins, it is likely to confer BBB integrity in a vessel-segment specific manner, underscoring heterogeneity of BBB regulation in different vascular segments 39 .…”
Section: Discussionmentioning
confidence: 99%